Case report: Therapeutic approach to secondary polycythemia vera in an adult with eisenmenger syndrome - Lil Alamin, Rahmatan; Raharjo, Fajar; Gunawan, Michelle; Wardhani, Shinta (Deka in Medicine, 2024)
BACKGROUND: Secondary Polycythemia Vera due to Eisenmenger Syndrome remains a big challenge, and the reported cases regarding this condition are still scanty. CASE: This was a case of a 22-year-old girl who, since childhood, had complaints of fatigue most of the time and thus showed more intolerance to heavy physical work. She had a history of a congenital heart defect, with lip and finger cyanosis that increased upon fatigue, and she had undergone Bi-directional Cavo-pulmonary Shunt. Physical examination showed cyanosis with clubbing of fingers with low oxygen saturation. Further diagnosis testing revealed this was a case of Eisenmenger Syndrome due to congenital heart abnormalities, with Polycythemia Vera: Secondary to the diagnosis. The patient also had a hemoglobin level of 21.1g/dL and a hematocrit level of 64.2%. Based on the diagnosis, treatment was given in the form of hydration therapy along with medications. Additionally, phlebotomy was performed. Because the patient improved clinically from the applied treatment, the patient was discharged after 5 days. CONCLUSION: Early diagnosis, a multidisciplinary approach, and proper interventions are important in the management of Eisenmenger Syndrome and associated Polycythemia Vera to avoid complications and hence improve outcomes.